Medication Adherence in Post Myocardial Infarction Patients at Shahid Gangalal National Heart Centre - Giri, Madhu; Shakya, Rajani; Bista, Durga; Manandhar, Aastha; Giri, Dikshya (Nepalese Heart Journal, 2022)
Background and Aims: Medication adherence among Post myocardial infarction (MI) patient is suboptimal all over the world. Although significant advances have been made in the diagnosis and management of Acute Myocardial Infraction, it is still a major cause of morbidity and mortality worldwide and significant therapeutic challenges to the society. The purpose of the study was to study the medication adherence and to identify the effect of adverse drug reaction (ADR) on medication adherence. Methods: The study was a single center, prospective study carried out in Shahid Gangalal National Heart Centre (SGNHC) in Nepal. The enrolled patients were followed up at 6th weeks after discharge in outpatient department (OPD) visit. Patients were interviewed with Morisky Green Levine (MGL) adherence scale questionnaire to identify medication adherence. The ADR was assessed. Data were analyzed in SPSS version 20. Results: A total of 134 patients were included in the study. The study showed post MI patient were highly adherent to medication (92.5%). ADR was not significantly associated with medication adherence. Conclusion: Patients were highly adherent to medication and the effect of ADR on medication adherence was not significant.